2021
DOI: 10.1111/tmi.13579
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section rate in Nigeria between 2013 and 2018 by obstetric risk and socio‐economic status

Abstract: objectives Caesarean section (CS) can be life-saving for both mother and child, but in Nigeria the CS rate remains low, at 2.7% of births. We aimed to estimate the rate of CS and early neonatal mortality in Nigeria according to obstetric risk and socio-economic background and to identify factors associated with CS.methods We used the 2018 Nigeria Demographic and Health Survey, encompassing 33 924 live births within the last 5 years, to estimate the CS rate and early neonatal mortality rate (ENMR) by obstetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Aside from the limited access to caesarean deliveries in SSA, there are vast within-country disparities in the use of caesarean deliveries, largely due to socio-economic and demographic inequalities [ 1 , 9 ] Factors such as maternal age, education, wealth, parity, number of antenatal care visits, religion, ethnicity, health insurance coverage, employment status, reproductive history, and place of residence contribute significantly to the use of caesarean deliveries in SSA [ 1 , 13 , 14 ] In Nigeria, for example, higher odds for caesarean delivery were observed among women with a higher number of antenatal care visits, higher educational attainment, multiple pregnancies, higher household wealth, and among Christians [ 14 ]. In Burundi, higher rates of caesarean deliveries were observed among wealthy women, those with higher educational levels, and those living in urban areas [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the limited access to caesarean deliveries in SSA, there are vast within-country disparities in the use of caesarean deliveries, largely due to socio-economic and demographic inequalities [ 1 , 9 ] Factors such as maternal age, education, wealth, parity, number of antenatal care visits, religion, ethnicity, health insurance coverage, employment status, reproductive history, and place of residence contribute significantly to the use of caesarean deliveries in SSA [ 1 , 13 , 14 ] In Nigeria, for example, higher odds for caesarean delivery were observed among women with a higher number of antenatal care visits, higher educational attainment, multiple pregnancies, higher household wealth, and among Christians [ 14 ]. In Burundi, higher rates of caesarean deliveries were observed among wealthy women, those with higher educational levels, and those living in urban areas [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have investigated rural–urban differences in the use of caesarean deliveries in SSA [ 3 , 4 , 10 , 14 ], most of these studies were conducted at the individual country level. Thus, there are limited multi-country analyses of rural–urban disparities in the use of caesarean deliveries in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…We derived the CS rates in health facilities by dividing the overall CS rate by the percentage of deliveries in health facilities extracted from the 2006 and 2014 MICS [ 21 , 28 ]. Following Boerma et al method, we computed the average annual rates of increase (AARI) in CS rates, health facility deliveries, and CS deliveries in health facilities as ln (value in 2014/value in 2006)/8 years [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies from other developing countries, showed the rural-urban divide in the CS rates as well as difference by geographical regions and wealth [20][21][22][23][24]. The present study aimed to document the CS rate in Sudan at the national level, and assess its changing patterns over time, across geographical regions, area of residence, and wealth.…”
Section: Introductionmentioning
confidence: 93%
“…This is undesirable, given the attending high level of maternal mortality arising from preventable causes of death in society. 27 29 …”
Section: Introductionmentioning
confidence: 99%